Komuniciranje trajnostnosti na primeru ekoloških turističnih kmetij v Sloveniji - Lipavic Oštir, Alja (Komuniciranje okoljske krize, 2025)
The contribution analyzes the online communication of organic tourist farms in Slovenia. The tourist offer of the analyzed farms is characterized by the ecological orientation of the farm, the diversity of organic products and services, location close to less degraded nature, the family as the foundation of operations, respect for tradition, the importance of the farm's and the environment’s heritage, individuality in the development of tourism activities, appropriate culinary offerings, and various accommodation options. The commitment to sustainable practices is part of the farms’ core beliefs. It is accompanied by family cohesion and the preservation of traditions and cultural heritage. This is partly reflected in the individual farm slogans. The environmental policies and practices of the farms cover all areas of operation, including their attitude toward guests. The specific culinary offerings of these farms are marked by three key elements: organic, local, and seasonal. The analyzed farms provide opportunities for various experiences, which meet the expectations of today’s tourists. In successfully presenting their sustainable tourism products, the use of narratives stands out. The farms’ logos partly support the development of sustainability. A joint market presence of these farms would yield better results and encourage the development of organic tourism.